Stories from a hazardscape : living with chronic illness in Petone, Aotearoa New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science with an endorsement in Health Psychology at Massey University, Wellington, Aotearoa New Zealand - Kearns, Nardia (Massey University, 2022)
Natural hazards such as earthquakes, flooding, and landslides can disrupt routine medical treatment for people living with chronic illness including heart disease, diabetes, asthma, and renal failure, causing people’s conditions to deteriorate (Miller & Arquilla, 2008). Studies of past events have shown that the chronically ill as a group face the greatest risk of adverse health outcomes from a natural hazard and require the most medical treatment after an event compared with other groups (Tomio & Sato, 2014). However, for a range of reasons, emergency management plans provide little or no specific planning for people with chronic illnesses, focussing instead on the needs of people critically injured by a natural hazard (Miller & Arquilla, 2008). In the event of a disaster, the lack of focussed planning for the chronically ill has resulted in people becoming acutely ill or dying because of lack of medication and other essential medical treatment (Tomio & Sato, 2014). This study set out to improve understanding of people’s experience of living with a chronic illness in Petone, a hazard prone environment, and how this may matter to their ongoing health and wellbeing. The narratives of eight people with a range of chronic illnesses and who had lived in Petone were analysed and interpreted through applying a critical narrative methodology as well as a Foucauldian lens to their stories. Semi-structured face-to-face narrative interviews were conducted, enabling people to share their stories of life in Petone with a chronic illness. Analysis of the eight people’s stories was guided by the Narrative Orientated Inquiry model. The premise behind this model is that narratives function as a meaning making process that occur within social, psychological, and cultural contexts (Hiles, Cermák, & Chrz, 2009; E. G. Mishler, 1995; Riessman, 2008). The model incorporates this concept of narrative into each stage making it possible to carry out a deeper analysis of the contents of stories and exposing the functioning of storytelling (e.g. social processes), which is important to how people structure and organise behaviour and experience (Hiles, Čermák, & Chrz, 2017). With little research exploring the lived experience of people with chronic illness living in hazard prone areas, this narrative-based study benefits the health and emergency management sector by providing insight into the specific needs of the chronically ill. It also demonstrates the significance of the experience of the chronically ill with managing their illness generally, and suggests that this experience might be a valuable knowledge resource for emergency management planning.
Keywords: 520304 Health psychology